Extending the classification of European countries by their IFRS practices: a research note - Lourenço, I. C.; Sarquis, R.; Branco, M. C.; Pais, C. (Accounting in Europe, 2015)
This paper expands the IFRS accounting systems' classification proposed by Nobes [(2011). IFRS practices and the persistence of accounting system classification. Abacus, 47(3), 267-283] to a broader set of European countries. The results suggest a classification distinguishing between four groups of European countries, and add to the evidence, reported by Kvaal and Nobes [(2010). International differences in IFRS policy choice. Accounting and Business Research, 40(2), 173-187] and Nobes (2011)., that pre-IFRS accounting differences influence the options adopted by firms. This study contributes to the literature suggesting that the widespread adoption of IFRS has not eliminated the differences between national accounting practices and that accounting systems classification did not lose its relevance.